Novel Synthesis of Functionalized Indolizine Derivatives from Huisgen’s Zwitterions and 1-Methylimidazole/Dichloroketene Adduct - Yavari, Issa; Hosseinpour, Reza; Pashazadeh, Ramin; Skoulika, Stavroula (Synlett, 2012)
The reactive zwitterionic intermediates, generated from addition of pyridine derivatives to dialkyl acetylenedicarboxylates, react with 1-methylimidazole/dichloroketene adduct to afford functionalized dialkyl 1-(2,2-dichloroacetyl)indolizine-2,3-dicarboxylates in moderate yields.
Keywords: indolizine; acetylenic ester; dichloroacetyl chloride; 1-methylimidazole; N-heterocycle